Optical v-conformable normalized and recursional electroosmotic optimistic v-conformable energy - Korpinar, Talat; Korpinar, Zeliha; Asil, Vedat (Springer, 2024)
In this paper, we describe v-conformable normalization and v-conformable recursional of electromagnetic fields in conformable spherical space. Then, we obtain normalized and recursional v-conformable electroosmotic rho(tau), p(v), rho(beta) optimistic v-conformable energy. Finally, we have optical microfluidic v-conformable normalized and recursional electroosmotic rho(tau), p(v), rho(beta) optimistic v-conformable energy in conformable spherical space.
Keywords: Optical recursion; Conformable spherical space; Microfluidic microscale; Normalized optimistic density